Mutations of MACF1, Encoding Microtubule-Actin Crosslinking-Factor 1, Cause Spectraplakinopathy - Kang, Lulu; Liu, Yi; Jin, Ying; Li, Mengqiu; Song, Jinqing; Zhang, Yi; Zhang, Yao; Yang, Yanling (Frontiers in Neurology, 2020)
As a member of spectraplakin family of cytoskeletal crosslinking proteins, microtubule-actin crosslinking factor 1 (MACF1) controls cytoskeleton network dynamics. Knockout of Macf1 in mice resulted in developmental retardation and embryonic lethality. Spectraplakinopathy type I, a novel neuromuscular condition characterized by periodic hypotonia, lax muscles, joint contracture, and diminished motor skill, was reported to be associated with heterozygous genomic duplication involving the MACF1 loci, with incomplete penetrance and highly variable clinical presentation in a single pedigree. In this study, parental-derived compound heterozygous novel missense mutations of MACF1, c.1517C>T (p.Thr506Ile) and c.11654T>C (p.Ile3885Thr), were found to cosegregate with disease status in two affected brothers presenting with progressive spastic tetraplegia, dystonia, joint contracture, feeding difficulty and developmental delay. We speculated that MACF1 mutations cause spectraplakinopathy inherited in an autosomal recessive manner. Our clinical findings expanded the phenotype of this neuromuscular disorder and provided new insights into the function of MACF1.